2023
DOI: 10.1002/adma.202210769
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Processing: Complex Coacervates as Versatile Inks for 3D Bioprinting

Abstract: 3D bioprinting is a powerful fabrication technique in biomedical engineering, which is currently limited by the number of available materials that meet all physicochemical and cytocompatibility requirements for biomaterial inks. Inspired by the key role of coacervation in the extrusion and spinning of many natural materials, hyaluronic acid–chitosan complex coacervates are proposed here as tunable biomaterial inks. Complex coacervates are obtained through an associative liquid–liquid phase separation driven by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…For example, recently, we showed that the 3D printability, and more precisely the shape retention ability, of HA−CHI complex coacervates can be controlled by changing the pH during processing. 10 We observed a higher extent of shape retention as well as slower dynamics at pH values closer to the pKa of the CHI chains and assigned this to the relative insolubility of the chains.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…For example, recently, we showed that the 3D printability, and more precisely the shape retention ability, of HA−CHI complex coacervates can be controlled by changing the pH during processing. 10 We observed a higher extent of shape retention as well as slower dynamics at pH values closer to the pKa of the CHI chains and assigned this to the relative insolubility of the chains.…”
Section: Introductionmentioning
confidence: 62%
“…More specifically, being able to control the liquid-to-solid transition of complex coacervates by (gradual) changes in pH, salt, or other parameters will enable the formation of novel polyelectrolyte materials. For example, recently, we showed that the 3D printability, and more precisely the shape retention ability, of HA–CHI complex coacervates can be controlled by changing the pH during processing . We observed a higher extent of shape retention as well as slower dynamics at pH values closer to the p K a of the CHI chains and assigned this to the relative insolubility of the chains.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Reproduced with permission from Khoonkari et al. [ 190 ] (C) Polyacrylic acid–isoprenyl oxy poly(ethylene glycol)/tannic acid coacervate, which has good adhesion and self‐healing capabilities, allowed the skin wound of Sprague–Dawley rats (8 weeks old) to recover well within 14 days. Reproduced with permission from Wang et al.…”
Section: Applicationsmentioning
confidence: 99%
“…Therefore, besides shear‐thinning behavior and fast self‐healing, maintaining the relaxation dynamics of coacervates within a reasonable range is the key to making coacervate materials that both possess acceptable plasticity and structural rigidity. [ 190 ]…”
Section: Applicationsmentioning
confidence: 99%